Low-Dose Resveratrol Inhibits RIPK3-Mediated Necroptosis and Delays the Onset of Age-Related Hearing Loss - Yang, Zeyin; Zhang, Yan; Yang, Shuling; Ding, Yongqing; Qu, Yan (Frontiers in Pharmacology, 2022)
Background: To investigate the pathophysiology of age‑related hearing loss (ARHL) and the mechanism of resveratrol (RSV) in prevention and treatment of ARHL. Methods: C57BL/6 mice of different ages were used in this study. Auditory brainstem response (ABR) was performed to assess hearing and identify abnormalities. Surface preparation and hair cell-specific marker Myo VIIa were employed to evaluated cochlear hair cell losses. Scanning electron microscopy (SEM) was to observe the microstructure of the organ of Corti (OC). The expression of related proteins in the RIPK1/RIPK3/MLKL pathway in cochlear tissue was detected by immunofluorescence. Results: In old mice (15 months), the ABR threshold increased significantly compared with the young mice. After 50 mg/kg RSV intervention, the hearing threshold of the old mice was significantly reduced at 8 kHz and 12 kHz as well as click. 100 mg/kg RSV led to a statistically significant reduction in hearing threshold only at clicks, whereas 300 mg/kg RSV showed no difference at all frequencies tested. In terms of cochlear hair cell loss, the damage of OHC and IHC was severe in old mice, but the damage was evidently reduced in RSV 50 mg/kg group. Notably, in the RSV 300 mg/kg group, the loss and disorientation of both the OHCs and IHCs were aggravated. Under SEM, a large number of OHCs were lost in the old group, but increased significantly in the RSV 50 mg/kg group, and even the OHCs were more seriously damaged in the RSV 300 mg/kg group. Furthermore, immunofluorescence showed that 50mg/kg RSV significantly reduced the expression of RIPK3, RIPK1, and MLKL in the cochlea during aging, especially in necroptosis-sensitive regions OCs and SGN. Conclusions: Low-dose RSV inhibited RIPK3-mediated necroptosis in aging cochlea and delayed the onset of ARHL, which was a promising therapeutic strategy for ARHL.